2023
DOI: 10.3390/ijms24021419
|View full text |Cite
|
Sign up to set email alerts
|

Basic Helix-Loop-Helix Transcription Factors: Regulators for Plant Growth Development and Abiotic Stress Responses

Abstract: Plant basic helix-loop-helix (bHLH) transcription factors are involved in many physiological processes, and they play important roles in the abiotic stress responses. The literature related to genome sequences has increased, with genome-wide studies on the bHLH transcription factors in plants. Researchers have detailed the functionally characterized bHLH transcription factors from different aspects in the model plant Arabidopsis thaliana, such as iron homeostasis and abiotic stresses; however, other important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 159 publications
0
8
0
Order By: Relevance
“…Basic helix-loop-helix (bHLH) TFs play a crucial roles in a variety of processes of plant growth, metabolism, and abiotic stress response ( Zuo et al., 2023 ). However, the characterization of bHLH genes in P. sibirica has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Basic helix-loop-helix (bHLH) TFs play a crucial roles in a variety of processes of plant growth, metabolism, and abiotic stress response ( Zuo et al., 2023 ). However, the characterization of bHLH genes in P. sibirica has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A standard bHLH domain is usually composed of two parts, including a basic region positioning at the N-terminus of bHLH domain, which is known to recognize and bind to the E-box consensus (CANNTG), followed by a HLH region positioning at the C-terminus of the bHLH domain that is accountable for homo- and heterodimer formation [ 14 ]. The bHLH TFs engage in a multitude of physiological events, from plant growth and development (e.g., embryo growth, anthers development, fruit dehiscence, and seed dispersal) to stress adaptation (e.g., pathogen infection, cold stress, and salt stress) [ 15 ]. Currently, some bHLH proteins that are involved in fruit ripening regulation have been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…A number of evidence has shown that bHLH family genes are involved in plant development processes [21,22]. For example, the bHLH TF SPATULA (SPT) inhibited root growth and size through limiting cell proliferation and expansion in Arabidopsis [23].…”
Section: Introductionmentioning
confidence: 99%